Distinct contributions of hippocampal pathways in learning regularities and exceptions revealed by functional footprints - Melisa Gumus; Michael L. Mack (Proceedings of the National Academy of Sciences, 2026)
Fundamental aspects of learning are theorized to be supported by hippocampal pathways: The monosynaptic pathway (MSP) extracts regularities, whereas the trisynaptic pathway (TSP) rapidly encodes exceptional items. Yet, the empirical evidence for the dynamic involvement of MSP and TSP in learning remains unresolved. We leveraged diffusion-weighted imaging to estimate the endpoints of MSP- and TSP-related white matter structures (i.e., footprints) within hippocampal subfields and the entorhinal cortex. We then measured the activation of pathway-specific footprints with functional MRI while participants learned novel concepts defined by regularities and exceptions. The functional footprint method revealed links between MSP-related footprint activation and regularity encoding early in learning and TSP-related footprint activation and exception encoding late in learning. These findings provide empirical evidence that learning concept regularities and exceptions is preferentially supported by hippocampal pathways. The pathway footprint approach provides insights into the functional dynamics of the human hippocampus, translating theoretical and computational work into empirically testable questions in humans.